2011
DOI: 10.1111/j.1754-9485.2011.02271.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiology of vernix caseosa peritonitis: Case report and discussion

Abstract: Vernix caseosa peritonitis is a rare complication of pregnancy that can occur following Caesarean section. If fetal vernix enters the peritoneal cavity, it may incite an acute inflammatory response leading to peritonitis. This diagnosis should be considered when patients present with an acute abdomen pain following Caesarean section. Radiological imaging may identify lesions in the abdominal wall wound or peritoneal cavity, and the diagnosis can be made by image-guided biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Diagnosis is often difficult due to lack of awareness of the condition and may only be made following histologic examination. The characteristic intraoperative finding is a cheesy white exudate that coats the visceral organs, which are not inflamed themselves (18,19). Histologic examination of the cheesy exudates is the only way to diagnose VCP.…”
Section: Vernix Caseosa Peritonitismentioning
confidence: 99%
“…Diagnosis is often difficult due to lack of awareness of the condition and may only be made following histologic examination. The characteristic intraoperative finding is a cheesy white exudate that coats the visceral organs, which are not inflamed themselves (18,19). Histologic examination of the cheesy exudates is the only way to diagnose VCP.…”
Section: Vernix Caseosa Peritonitismentioning
confidence: 99%
“…A recent study showed that radiological imaging may identify lesions in the abdominal wall or peritoneal cavity, and diagnosis can be made by image-guided biopsy. 1 However, this may not be always practical and many patients undergo surgical exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Vernix caseosa peritonitis (VCP) is a very unusual complication caused by inflammatory response to amniotic fluid spilled into the maternal peritoneal cavity; only 27 cases of this entity have been reported in literature 13. All the cases reported occurred after cesarean section 118.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study published in 2011 reports that VCP could be diagnosed with image guided biopsy 15 although this may not be practical in the presence of peritonitis and SIRS. Most women in this cohort of patients, in corroboration with our case, progressed to emergency laparotomy and organ resection for presumed diagnoses of more common causes of peritonitis (appendicitis, bowel/ureteric injury or uterine rupture).…”
Section: Discussionmentioning
confidence: 99%